2010
DOI: 10.1042/bj20100305
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein and growth differentiation factor cytokine families and their protein antagonists

Abstract: The BMPs (bone morphogenetic proteins) and the GDFs (growth and differentiation factors) together form a single family of cystine-knot cytokines, sharing the characteristic fold of the TGFbeta (transforming growth factor-beta) superfamily. Besides the ability to induce bone formation, which gave the BMPs their name, the BMP/GDFs display morphogenetic activities in the development of a wide range of tissues. BMP/GDF homo- and hetero-dimers interact with combinations of type I and type II receptor dimers to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
200
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(202 citation statements)
references
References 148 publications
(119 reference statements)
0
200
1
1
Order By: Relevance
“…Differential BMP-mediated pSmad1/5/8 signalling and Gremlin1 inhibition in kidney epithelial cells BMP binding to heterotetrameric type I/II receptor complexes leads to Smad1/5/8 phosphorylation, dimerization with co-Smad4, nuclear translocation and transcriptional activation [2]. To validate the SPR and MST protein interaction data in a cell culture system, human kidney proximal tubule epithelial cells (HK-2) were incubated with increasing concentrations of rhBMPs (BMP-2; 0.5 ng/ml-10 ng/ml, (39-790 pM), BMP-4; 0.5 ng/ml-10 ng/ml, (39-780 pM) or BMP-7; 5-50 ng/ml (325 pM-3.25 nM)).…”
Section: Recombinant Gremlin1 Binds Bmps With Different Affinitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Differential BMP-mediated pSmad1/5/8 signalling and Gremlin1 inhibition in kidney epithelial cells BMP binding to heterotetrameric type I/II receptor complexes leads to Smad1/5/8 phosphorylation, dimerization with co-Smad4, nuclear translocation and transcriptional activation [2]. To validate the SPR and MST protein interaction data in a cell culture system, human kidney proximal tubule epithelial cells (HK-2) were incubated with increasing concentrations of rhBMPs (BMP-2; 0.5 ng/ml-10 ng/ml, (39-790 pM), BMP-4; 0.5 ng/ml-10 ng/ml, (39-780 pM) or BMP-7; 5-50 ng/ml (325 pM-3.25 nM)).…”
Section: Recombinant Gremlin1 Binds Bmps With Different Affinitiesmentioning
confidence: 99%
“…To date, however, efforts to translate these data into BMP-7-centred treatment of fibrosis have been rather slow to develop [18,19] Canonical BMPs signalling involves the Smad pathway, where BMP dimers bind to type I and type II BMP receptors leading to the formation of a hexameric complex, triggering receptor phosphorylation. This leads to phosphorylation of R-Smads (Smad1/5/8) and complex formation with co-Smad4 which translocates to the nucleus to regulate BMP target gene expression [1,2]. BMP target genes include inhibitor of differentiation (Id 1-3) genes and inhibitory Smad 6 [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone morphogenic proteins (BMPs) belong to the TGFβ family and regulate proliferation and differentiation of both mesenchymal cells and epithelial cells (Rider and Mulloy, 2010). Recent studies have revealed that BMP7 prevents fibrosis by promoting epithelial regeneration, while BMP antagonists such as gremlin and ectodin drive organ fibrosis by inhibiting BMP7 signaling.…”
Section: Regulation Of Fibrosis By Inflammatory Mediatorsmentioning
confidence: 99%